Accreditation Automation System to Improve the Quality of Education - Mayulu, Hamdi; Tricahyadinata, Irsan (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This research aims to design and implement an automated accreditation system to enhance educational quality. An exploratory approach was used, employing a literature review sourced from high-quality databases such as Web of Science, Scopus, and PubMed. The keywords utilized were “Quality Assurance in Higher Education” and “Automation System.” Inclusion criteria were articles published in the last ten years (2015-2024) to ensure the review's relevance, full texts written in English, and discussions regarding quality assurance in higher education. The results of the system implementation showed a significant increase in efficiency, reducing the accreditation processing time by up to 50%. Transparency in the accreditation process improved, making information more accessible to all stakeholders. The automation system allowed for active user participation, enabling real-time feedback and facilitating process adjustments. The use of automated assessment algorithms and data visualization contributed to reducing manual errors and enhancing assessment objectivity. This research significantly contributes to the development of a more responsive and quality-oriented accreditation system, supporting efforts to enhance educational quality in an increasingly competitive global landscape